Guidelines to the fourth plan : proceedings of the 1980 symposium - Nigerian Economic Society; University of Ibadan (Ibadan, Nigeria : Nigerian Economic Society, Dept. of Economics, University of Ibadan, 1981)
This covers a review of the guidelines for the Fourth National Plan to ensure that the deliberations attain more than mere academic status
osc 04/04/2019
Arch
Keywords: Economic planning; Nigeria